The Medicago truncatula lncRNA ENOD40 is a mediator of microRNA169 -controlled NF-YA activity in nodule initiation - Tristan Wijsman; Nadia A. Mohd-Radzman; Jieyu Liu; Giles E. D. Oldroyd; Wouter Kohlen; Olga Kulikova; Renze Heidstra; Ben Scheres; Henk J. Franssen (Proceedings of the National Academy of Sciences, 2025)
The hallmark of the legume lncRNA EARLY NODULIN40 ( ENOD40 ), involved in rhizobium-induced nodulation, is the presence of a highly conserved stretch of 24 nucleotides, designated box2, preceded by a small open-reading-frame (sORF) coding for a peptide of 12 to 13 amino acids. Although there is a well-established link between ENOD40 and nodulation, it is not fully clear by which mechanism ENOD40 functions in this process. Here, we show that a region harboring box2 can complement nodule formation in an ENOD40 knock-out mutant ( enod40-1-2/1 ). The sequence of box2 bears the characteristics of a miR169 target mimic. We show that the artificial target mimic MIM169defg can indeed complement the reduced capability of nodule formation in enod40-1-2/1 , and that box2 exhibits target mimic activity in a transient luciferase assay. In addition, the introduction of a miR169 -resistant form of MtNF-YA1 also elevates the capacity to form nodules in enod40-1-2/1. We conclude that ENOD40 effectuates nodule initiation by posttranscriptional upregulation of the miR169 target NF-YA1 , which encodes an essential transcription factor in this step of the nodulation process.